Objectively measured physical activity in population-representative parent-child pairs: parental modelling matters and is context-specific - Bettina Bringolf-Isler; Christian Schindler; Bengt Kayser; L. Suzanne Suggs; Nicole Probst-Hensch; the SOPHYA Study Group (BMC, 2018)
Abstract Background Evidence for the context-specific influence of parental modelling on physical activity (PA) in childhood remains inconclusive. This nationwide Swiss study assessed the cross-sectional association between objectively measured PA of parents and their children and whether it varied across different levels of sociodemographic and environmental factors. In a second step a structural equation-model (SEM) was used to assess, whether associations between children's PA and sociodemographic and environmental factors are mediated by the parental PA behaviour. Methods The population-based sample of the SOPHYA-study consisted of 889 children aged 6 to 16 years living in Switzerland and 1059 parents. PA was measured using accelerometers. Information on sociodemographics, sports behaviour, family characteristics, and perceived environment was obtained by telephone interview and parental questionnaire. Objective environmental data was allocated to each family's residential address using GIS (geographic information system). A structural equation model tested these factors for both independent associations with children's PA and associations mediated through the parental PA behaviour. Results Parental moderate to vigorous physical activity (MVPA) was associated with MVPA of their children in general (p < 0.001). Correlations between parents' and children's MVPA were stronger for children aged 10-12 years and for those living in the Italian speaking part of Switzerland. An increase of 1 min of mother's and of father's MVPA was associated with 0.24 and 0.21 min more MVPA in children, respectively. Father's PA was associated with that of their sons, but not with that of their daughters, whereas the association of mothers' and children's PA did not depend on the parent-offspring sex-match. The pathway analysis in our structural equation model showed direct effects on children's MVPA as well as indirect effects mediated by the parental PA behaviour. Conclusions Parental modelling seems relevant for children's PA, but not to the same degree in all children. Interventions focusing on strengthening parental PA behaviour for the promotion of PA in the young must consider additional contextual factors related to the socio-cultural and structural environment.